Lessons for the NFL from Workers’ Compensation - Diana, Richard (The Hastings Center report, 2016)
In the article “A Proposal to Address NFL Club Doctors’ Conflicts of Interest and to Promote Player Trust,” Glenn Cohen et al. write, “The [NFL's] current structure forces club doctors to have obligations to two parties—the club and the player—and to make difficult judgments about when one party's interests must yield to another's.” I can understand why some might be suspicious about bias in the current NFL medical system, in which the club doctors have a professional duty to put their player-patients’ best interests first yet are employed by clubs, which have a primary goal of winning football games. It is my opinion, however, that neither the club nor the player needs to be sacrificed. I base this opinion partly on my experience as an NFL player in the early 1980s, partly on several years as team physician for the Boston Red Sox, and partly on my twenty-three-years of experience as a physician with the Connecticut Workers’ Compensation medical system, which supposes that physicians can be fair to both workers and employers.